Transverse compressive properties of unidirectional GFRP composites: Size effect, elevated temperature, and cyclic freezing-hydrothermal aging - Liu, Qian; Shi, Zheng; Liu, Xiaogang (Construction & building materials, 2025)
The unidirectional glass fiber reinforced polymer (GFRP) composites in engineering applications may be subject to transverse compression and harsh environmental action. Through analysis of the macroscopic testing failure modes, microscopic failure morphology utilizing scanning electron microscopy, and the stress-strain relationships, this research investigates the transverse compressive properties of unidirectional GFRP composites, exploring the effect of testing size effect, elevated temperatures, and cyclic cryo-thermal aging. The results indicate that the transverse compression failure generally manifests as a diagonal crack crossing the fiber-resin interface, and testing specimens with a height-to-width ratio over 2.0 exhibit a non-significant size effect. Additionally, the elevated temperature effect results in reduced matrix stiffness and a degradation of the fiber-matrix interface. The compressive strength degrades linearly with elevated temperature; the compressive modulus degrades slightly before the resin state transition from a glassy state to a rubber state begins (within 80ºC), but acceleratingly degrades afterward until glass transition temperature Tg (about 120ºC); both the strength and modulus retention ratios are lower than 10 % at Tg. The cyclic cryo-thermal aging has contradictory effects, inducing beneficial post-curing effects of the resin matrix and unfavorable fiber-resin interface degradation; it has a non-significant influence on the macroscopic transverse compressive strength but changes the microscopic failure mechanism. •Investigating transverse compression properties of unidirectional GFRP composites.•Exploring effect of elevated temperatures and cyclic cryo-thermal aging.•Clarifying transverse properties degradation law at elevated temperatures.•Discussing cyclic-cryo-thermal aging effect and analyzing its mechanism.